Towards an integrated framework for understanding social-ecological interactions: nature’s contributions to people meets cultural ecosystem services - Kim C. Zoeller; Graeme S. Cumming (Ecosystems and People)
The social and cultural elements of human interactions with nature remain among the least-studied and least understood elements of social-ecological systems. Although the conceptual framework of the Intergovernmental Science-Policy Platform on Biodiversity and Ecosystem Services (IPBES) provides an entry point into assessing nature’s contributions to people (NCP), at face value IPBES has limited capacity to capture subjective elements of values and culture as influences on important socio-cultural processes that underpin social-ecological interactions. We propose that integrating cultural ecosystem services more explicitly into the IPBES conceptual framework can help fill its existing gaps by 1) elucidating the social-cultural mechanisms that underpin the production and valuation of non-material NCP, 2) explaining the role of heterogeneity in cultural, social and environmental processes, 3) identifying the two-way interactions between nature and people that co-produce NCP, and 4) identifying synergies between the IPBES conceptual framework and the cultural ecosystem services approach that will facilitate the application of the IPBES framework in more diverse settings. We use recently published work on cultural ecosystem services associated with birds to illustrate our suggestions in action. Assessing social-ecological systems through this adapted framework makes implicit connections easier to draw out, thereby providing holistic insight into the feedbacks and linkages that should be considered at all levels of environmental decision-making.